Address of His Grace the Archbishop of Dublin [at the first Annual Meeting of the Social Inquiry Society of Ireland] - Whately, Richard (Social Inquiry Society of Ireland, 1851)
His Grace expressed his great satisfaction at the establishment of such a society as that, which seemed to him calculated to meet in some, perhaps in a very great measure, one very great evil, which was essentially inseparable from a free government; he meant an evil resulting from party-contests. Every body must have observed ? although this was a well-governed country, perhaps the best in the world ? yet that in every branch of manufacture they succeeded better than in the manufacture of laws.
Address of His Grace the Archbishop of Dublin, President of the Society, at the Annual Meeting of the Society, 3rd November 1851
Keywords: Social Inquiry Society of Ireland; 314.15